Dexmedetomidine-Mediated Prevention of Renal Ischemia-Reperfusion Injury Depends in Part on Cholinergic Anti-Inflammatory Mechanisms. (April 2020) - Ma, Jianbo; Chen, Qian; Li, Juanjuan; Zhao, Hailin; Mi, Emma; Chen, Yan; Yi, Bin; Ning, Jiaolin; Ma, Daqing; Lu, Kaizhi; Gu, Jianteng
Abstract : BACKGROUND: Organ ischemia-reperfusion injury often induces local and systemic inflammatory responses, which in turn worsen organ injury. These inflammatory responses can be regulated by the central nervous system, particularly by the vagal nerve and nicotinic acetylcholine receptors, which are the key components of cholinergic anti-inflammatory pathway. Activation of the cholinergic anti-inflammatory pathway can suppress excessive inflammatory responses and be a potential strategy for prevention of ischemia-reperfusion injury of organs including the kidney. METHODS: Vagal nerve activity, plasma acetylcholine, catecholamine and inflammatory mediators, renal tissue injury, and cell death were measured in mice with bilateral renal ischemia/reperfusion with or without treatment with dexmedetomidine (Dex), an α2 -adrenergic receptor agonist. RESULTS: Dex significantly increased the discharge frequency of the cervical vagal nerve by up to 142 Hz (mean) ( P < .001), and preserved kidney gross morphology and structure and attenuated cell apoptosis after ischemia-reperfusion. Furthermore, Dex also significantly increased acetylcholine release to 135.8 pmol/L (median) when compared to that (84.7 pmol/L) in the sham group ( P < .001) and reduced the levels of several inflammatory mediators induced by renal ischemia/reperfusion. All the effects were abolished by vagotomy, splenectomy, or combinative administration of atipamezole, an α2 -adrenergic receptor antagonist. CONCLUSIONS: Our findings suggest that Dex provides renoprotection, at least in part, through anti-inflammatory effects of the parasympathetic nervous system activation in addition to its direct actions on α2 -adrenergic receptors.